Spectrophotometric Determination of Rabeprazole Sodium Using Two Charge Transfer Complexation Reactions - Mohamed H. Abdel-Hay, Suzy M. Sabry, Tarek S. Belal Ahmed A. Mahgoub (Journal of Applied Pharmaceutical Science, 2013)
This work presents two simple and direct spectrophotometric methods for determination of rabeprazole sodium (RB) through charge transfer complexation reactions. The first method is based on the reaction of the drug with p-chloranilic acid (p-CA) in acetonitrile to give a red colored product with maximum absorbance at 518 nm. The second method is based upon the interaction of RB and 7,7,8,8â€tetracyanoquinodimethane (TCNQ) in acetone resulting in the formation of a bluish-green complex measured at 845 nm. Factors affecting the color development were studied and optimized. The proposed colorimetric procedures were effectively validated with respect to linearity, ranges, precision, accuracy, robustness, detection and quantification limits. Regression analysis for the calibration curves of the formed color products with p-CA and TCNQ showed good linear relationships over the concentration ranges of 20–200 and 2–16 µg/mL respectively. The method was successfully applied to the assay of rabeprazole enteric coated tablets with good accuracy and precision. Assay results were statistically compared to a reference HPLC method where no significant differences were observed between the proposed methods and reference method.
Keywords: Rabeprazole sodium, Spectrophotometric Determination,Charge transfer complex, p-Chloranilic acid, TCNQ.